Nirmal Muṇdā Ḍāṅg āur Āmko, Simko, Loārām āndolana - Rautiā, Sunanda Siṃ (Oḍiśāra krtī ādibāsī santāna ;, 1996)
On the life of Nirmaḷa Muṇḍā, 1893-1973, leader of Munda agitation in Gangpur State, Orissa in 1939 and member of Orissa Legislative Assembly, 1957.